2014
DOI: 10.15376/biores.9.3.4063-4075
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation and Stability of Accelerated-curing Phenol-formaldehyde Resin

Abstract: In order to study the thermal stability of accelerated-curing PF resin, the curing behavior of fresh PF resin was investigated in the presence of single accelerator of methylolurea derivatives (MMU), magnesium hydrate (Mg(OH)2), 25% aqueous solution of sodium carbonate (Na2CO3), and propylene carbonate (PC). Also their optimum combination was added in fresh PF resin. The thermal stability of cured phenol-formaldehyde (PF) resins was studied using thermogravimetric analysis TG/DTA in air with heating rates of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The curing time was measured by adding NH 4 Cl hardener at the 3% level of resins at 100 °C according to the Ref. The measurements were done with three replications for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…The curing time was measured by adding NH 4 Cl hardener at the 3% level of resins at 100 °C according to the Ref. The measurements were done with three replications for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Hypothetically the stiffness of hot-pressed composites made from bamboo could be higher than the parent material, but the hot pressing regime used here does not appear to have been able to sufficiently stiffen the bamboo tissue. This is probably because the curing temperature of 150°C is in the upper range recommended for curing PF resin (Chen et al 2014), and the hot pressing duration under 7 min is lower than the optimal set of heat treatment conditions required to increase the strength and stiffness of bamboo tissue simply through heating; which are 180-200°C and over 20 min exposure (Schott 2006).…”
Section: Thickness Swell/water Absorptionmentioning
confidence: 99%
“…Previous works have shown that Na 2 CO 3 could accelerate phenolic resin curing, resulting in a short hot pressing time for the preparation of plywood panels . The distribution of ortho – para / para – para linkages and resin curing kinetics could be affected by the addition of carbonates was also reported .…”
Section: Resultsmentioning
confidence: 91%